Description of two new species of goby-associated snapping shrimps from the tropical western Pacific (Decapoda: Alpheidae: Alpheus) - Anker, Arthur (Zootaxa, 2022)
Two new snapping shrimps associated with gobies are described from the tropical waters of the western Pacific. Alpheus thompsoni sp. nov. is described based on a single adult female from Madang, Papua New Guinea. Alpheus sciolii sp. nov. is described based on several specimens of both sexes from the Solomon Islands, Australia and Vietnam. Both species are part of a larger species complex, which also includes A. djeddensis Coutière, 1897, A. djiboutensis De Man, 1909, A. bellulus Miya & Miyake, 1969, A. macellarius Chace, 1988, A. fenneri Bruce, 1994 and A. mannarensis Purushothaman, Abhilash, Kumar & Lal, 2021, but can be distinguished from each of them by a combination of morphological characters, and from the latter four species also by the very different colour patterns.